Perceptual representations of parametrically-defined and natural objects comparing vision and haptics - Gaissert, Nina; Wallraven, Christian (2010 IEEE Haptics Symposium, 2010)
Studies concerning how the brain might represent objects by means of a perceptual space have primarily focused on the visual domain. Here we want to show that the haptic modality can equally well recover the underlying structure of a physical object space, forming a perceptual space that is highly congruent to the visual perceptual space. By varying three shape parameters a physical shape space of shell-like objects was generated. Sighted participants explored pictures of the objects while blindfolded participants haptically explored 3D printouts of the objects. Similarity ratings were performed and analyzed using multidimensional scaling (MDS) techniques. Visual and haptic similarity ratings highly correlated and resulted in very similar visual and haptic MDS maps. To investigate to which degree these results are transferrable to natural objects, we performed the same visual and haptic similarity ratings and multidimensional scaling analyses using a set of natural sea shells. Again, we found very similar perceptual spaces in the haptic and visual domain. Our results suggest that the haptic modality is capable of surprisingly acute processing of complex shape.